Reading Guide Strategy Fosters Elementary Student Reading Comprehension Skill Mastery: Strategi Reading Guide Mendorong Penguasaan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Nabilatul Fikro; Reni Guswita; Nurlev Avana (Academia Open, 2026)
General Background Education aims to develop literacy foundations, particularly reading skills that are essential for elementary school subjects. Specific Background Fourth-grade students at SD Negeri 027/II Sungai Arang currently experience difficulties in vocabulary acquisition, identifying main ideas, and maintaining focus due to monotonous instructional methods. Knowledge Gap While guided reading frameworks exist, specific empirical studies observing the systematic application of guided questioning to resolve specific fourth-grade textual comprehension deficits remain limited. Aims This research investigates the application of a structured reading strategy to build text comprehension skills among fourth-grade pupils at SD Negeri 027/II Sungai Arang. Results Utilizing Classroom Action Research across two instructional cycles with 20 pupils, the analysis demonstrated an increase in the mean score from 64.2 to 84.6, alongside a learning mastery progression from 45 percent to 85 percent. Novelty This study details the progressive resolution of elementary literacy challenges through tailored pre-reading predictions, structured question guidelines, and guided text exploration. Implications Incorporating systematic reading guidelines serves as a highly supportive pedagogical approach for cultivating active student participation and achieving mastery of textual information. Highlights Classroom action research spanning two instructional cycles demonstrated a mean score progression from 64.2 to 84.6. Pupil learning mastery rates climbed significantly from 45 percent to 85 percent following targeted textual interventions. Structured pre-reading predictions and guided text exploration successfully stimulated active participation during literacy sessions. Keywords Reading Comprehension; Reading Guide Strategy; Elementary School Education; Classroom Action Research; Indonesian Language Learning